F 5 h 35 h2 45 h 5 325 10h h 2 2 0

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x + h) = 3( x + h) − 4(x + h) − 5 = 3( x + 2xh + h ) − 4 x − 4h − 5 = 3 x2 + 6x h + 3h2 − 4 x − 4h − 5 F. f( 5 + h) = 3(5 + h)2 − 4(5 + h) − 5 = 3(25 + 10h + h 2 ) − 2 0 − 4 h − 5 = 75 + 30h + 3h2 − 20 − 4h − 5 = 3h2 + 26h + 50 V. The difference quotient is so named because the operations involved are subtraction and division. Common forms of the difference quotient are: f ( x + h) − f(x) h f ( a + h) − f(a) B. h f ( 5 + h) − f(5) C. h D. f ( x + Δx ) − f(x) Δx A. The purpose for simplifying the difference quo...
View Full Document

Ask a homework question - tutors are online